Transport Properties of in-Plane $MoS_2$ Heterostructures from Lateral and Vertical Directions (Journal of Atomic and Molecular Sciences, 2016)
Two-dimensional (2D) molybdenum disulfide $(MoS_2)$ promised a wide rangeof potential applications. Here, we report the transport investigations on the $MoS_2$ from Armchair (AC) and Zigzag (ZZ) directions with different kinds of leads. Theconductance of 2H phase $MoS_2$ depended on the transport directions and lead types(2H phase or 1T phase). System with 1T phase $MoS_2$ as lead can impressively improvethe transport properties compared with the 2H phase lead. Moreover, for the systemwith metal lead, enhanced conductance can be observed, which contrast to the experimentmeasurements. Further investigation indicated that the conductance sensitivelyrelies on the distance between metal lead and 2D material. The present theoretical resultssuggested the lead material and interface details are both important for $MoS_2$ transport exploration, which can provide vital insights into the other 2D hybrid materials.
Keywords: lateral heterostructures; phase hybrid materials; $MoS_2$; transport.